2014
DOI: 10.1002/ccd.25280
|View full text |Cite
|
Sign up to set email alerts
|

New generation drug‐eluting stents for ST‐elevation myocardial infarction: A new paradigm for safety

Abstract: New generation DES in STEMI patients have less ST compared to BMS and trends for less ST compared to early generation DES. These data suggest a new safety paradigm and should encourage the use of new generation DES in most STEMI patients treated with primary percutaneous coronary intervention (PCI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…When we used standard adjustment and propensity score methods we found that DES use was associated with a significant reduction in mortality. This would be in keeping with previously reported observational analyses demonstrating an early survival benefit with DES [15,17]. Interestingly, we found no association with DES use and TVR using standard adjustment and propensity score methods.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…When we used standard adjustment and propensity score methods we found that DES use was associated with a significant reduction in mortality. This would be in keeping with previously reported observational analyses demonstrating an early survival benefit with DES [15,17]. Interestingly, we found no association with DES use and TVR using standard adjustment and propensity score methods.…”
Section: Discussionsupporting
confidence: 93%
“…Observational studies have demonstrated significant early and late reductions in mortality with DES [14][15][16][17], which differs to randomized trial data [3,4,13]. In a nonrandomized setting, BMS may be given to the sicker patients who are poor candidates for prolonged dual antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In this week's issue of CCI , Garg et al report an analysis of 3,464 STEMI patients treated with PCI using BMS, early generation (PES and SES) DES or new generation (EES and ZES) DES, at one of two busy primary PCI centers. The patients were prospectively enrolled into a database over an 8‐year period, and the primary operator determined the choice of stent at the time of intervention.…”
mentioning
confidence: 99%